ISO 14001 Certification: Benefits, Costs and Expectations for Organization - Di Noia, Alfredo Ernesto; Nicoletti , Giuseppe Martino (Studia Oeconomica Posnaniensia, 2016)
In the globalized market, the certification of Environmental Management Systems (EMS), according to ISO 14001 standard, introduced about 20 years ago and reviewed in 2015, is becoming increasingly strategic. In the last decade, the implementation of the EMSs was widely "metabolized" by organizations, because in this certification scheme, the decision maker recognizes, in the face of significant economic and organizational efforts, the opportunity to enjoy significant benefits from a variety of critical success factors. In fact, all over the world, the number of certified organizations has grown steadily. However, many organizations still tend to use the tool just because they are interested in grasping some "opportunities" (simplifications in permits, financial and banking incentives). Therefore, in some cases, there is a high risk that the certification may have the sole aim of improving the company's image, so-called "Green washing," while in other cases, the many changes required for the proper implementation of the certification create the belief that such a system is "much paper work and few benefits". In this work, we present the results of a survey of organizations certified with ISO 14001:2004 in the province of Foggia (Italy).